Preparation of Ethanol From Vegetable Waste Materials - RANJAN BHATTACHARJEE, PARTHA; YELHOUNGANBA KHUMAN, LAISHRAM; DE, BIPLAB; DEBBARMA, BIKASH; PAL (DATTA), SABITA (Asian Journal of Chemistry, 2010)
Ethanol was prepared by adopting the method of fermentation from vegetable waste followed by the techniques of conventional and indigenous which is generally practised by tribal people of Tripura, India. Manufactured ethanol is not free from methanol, claims moderate method for more purified ethanol. Dried residues can be used as cattle feed and tested in laboratory animals, showed good acceptance and devoid of any untoward action. It is eco-friendly and economical approach.